Organizational Culture in the Greek Science and Technology Parks: Implications for Human Resource Management. - Theodore Pelagidis; Thanos Kriemadis (European Regional Science Association (ERSA), 2006)
Introduction Research and technological poles have been also set up in Greek regions but only in the late '80s, introducing local economy into the modern international competitive environment. These infant cores of innovation have already inspired both academics and entrepreneurs to construct new models of investment planning and production. Although not yet fully developed, some of them, they have already created complex links between universities and industries, giving birth to many spin-off knowledge-based enterprises. Purpose of the Study and Organization of the Study This paper focuses on examining: (a) the four more successful case studies of Greek Science and Technological Parks, and (b) the organisational culture of the spin-off knowledge-based enterprises, within the Greek science and technology parks. It includes firms that have exited the parks but still have a close co-operation with them. Research Method The Organizational Culture Assessment Questionnaire (OCAQ) was developed by Sashkin (1996) to help people identify and understand the nature of the culture in their own organization. Sample and Data Collection The data for the present study were obtained by the OCAQ mailed to a sample of 33 spin-off companies which operate within the Science and Technological Parks of Greece. The mailing consisted of the questionnaire itself, a cover letter, and a stamped pre-addressed return envelope. As response inducement, each respondent was promised a copy of the study results on request. Of the 33 questionnaires mailed, 33 were received , representing a 100% response rate. Table 1 OCAQ Norms ManagingChange Achieving Goals Coordinated Teamwork CustomerOrientation Cultural Strength Total Very High 30 28-30 28-30 25-30 26-30 119 + High 26-29 23-27 24-27 21-24 22-25 108-118 Average 19-25 16-22 18-23 15-20 17-21 87-107 Low 15-18 11-15 14-17 11-14 13-16 76-86 Very Low 6-14 6-10 6-13 6-10 6-12 30-75 Results Table 2 presents a summary of respondents' mean scores as well as the total score for all companies involved in this study. Regarding Managing Change, the mean score is 15.82 and is considered low compared to the corresponding mean of the table of norms. According to Sashkin (1996), this area of action concerns how well the organization is able to adapt to and deal effectively with changes in its environment. All organizations are open, to some extent, to rapid technological and social change. The mean score for Achieving Goals is 15.03 and is considered low compared to the corresponding mean of the table of norms. Sashkin (1996) stated that having a clear focus on explicit goals as been proven repeatedly to have a very strong relationship to actual success and achievement. Regarding Coordinated Teamwork, the mean score is 13.96, again low compared to the corresponding mean of the table of norms. Sashkin (1996) believes that long term organizational survival depends on how well the efforts of individuals and groups within the organization are tied together, coordinated and sequenced so that people's work efforts fit together effectively. The mean score for Customer Orientation is 13.51 and is considered low compared to the corresponding mean of the table of norms. Sashkin (1996) argued that no matter how strong the culture and no matter how well the other functions of the organization are performed, if no one wants what the organization produces, then the organization is not likely to survive and prosper. Finally, the mean score for Cultural Strength is 13.67, again low compared to the corresponding mean of the table of norms. Sashkin (1996) stated that a strong culture based on values that support the functions of managing change, organizational achievement, customer orientation, and coordinated teamwork, will provide greater stability of organizational functioning. The total score 71.99 is very low compared to the corresponding one of the table of norms. However, Sashkin (1996) stated that the OCAQ is intended as a diagnostic aid, a first step in building better functioning organizational cultures. Through the OCAQ the company's management can probably get some feeling for what sort of numbers are "high" and what might be considered "low" from looking at Table 1. Most important is that the items that make up the scales provide concrete directions about what an organization might actually do to improve its culture. Table 2 Results of the Study ManagingChange Achieving Goals Coordinated Teamwork CustomerOrientation Cultural Strength N 33 33 33 33 33 MEAN 15.82 15.03 13.96 13.51 13.67 SD 2.25 2.49 3.35 2.79 3.37 Total Score: 71.99 Conclusions Sashkin (1996) stated that all organizations have a culture based on values and beliefs shared by some, most or all of the organization's members. However, when the culture is based on values that do not support the functions of managing change, organizational achievement, customer orientation, and coordinated teamwork, then this culture might actually hamper organizational survival and growth. Businesses of the Greek Science and Technological Parks need to adopt new approaches in attempting to change and manage effectively their organizational culture. Williams et al. (1993) suggested the following five methods commonly used by management: (a) Changing Human Resource management policies, management style and work environment. (b) Training employees in new skills and thus influencing their job attitudes. (c) Providing employees with training and role models appropriate to the desired culture, a culture which supports change, organizational achievement, customer orientation, and coordinated teamwork. (d) Greater emphasis on selecting people with the desired attitudes as well as technical skills and experience. This may include the use of more sophisticated selection techniques, for example psychometric testing, assessment centres, and biodata. (e) Moving people into new jobs to break up old sub-cultures. According to Whiteley (1991), the organization may use the following strategies to be customer driven: a. Information from customers is used in designing products/services b. The organization regularly asks customers to give feedback about its performance (satisfaction measures look at the extent to which customers are satisfied with the service they have received) c. Customers' complaints are regularly analyzed in order to identify quality problems d. Internal procedures and systems that do not create value for the customers are eliminated e. Employees are encouraged to go above and beyond to serve customers well f. Employees who work with customers are supported with continuous training and resources that are sufficient for doing the job well g. Employees are empowered to use their judgement when quick action is needed to make things right for a customer. Working as a team is a natural human behaviour. Everyone acts as part of a team, for the good of the entire organization. Dr.Deming also argued that competition is counterproductive inside an organization. The establishment of quality circles is a good example of teamwork. Quality circles consist of small groups of employees who meet to uncover and solve work-related problems. Members get together regularly to learn interpersonal skills and statistical methods associated with problem-solving and to select and solve real problems. Members meet an hour a week both during regular and outside of regular working hours. Meetings are chaired by a group leader. The leader is a discussion moderator who facilitates the problem-solving process. Problems are not restricted to quality, but also include productivity, cost, safety, morale, environment and other topics (Crocker, Charney and Chiu, 1984). Verespej (1990) found that the most important benefits to working in teams are: a) improved involvement and performance, b) positive morale, and c) sense of ownership and commitment to the product/service that teams create.
Keywords: 330